Pengaruh Kebijakan Pertahanan Pemerintah terhadap Hak Atas Tanah Masyarakat Adat - Anita Marianche; Rahjanto Rahjanto (Badan Strategi Kebijakan Hukum, 2010)
Regulation concerning land rights for indigenous people could have been there at the level of legislation and various government regulations, but the information is still rarely found in a simply and concisely. Meanwhile, the clarity of information on legal guarantee for indigenous people has been considered a pressing need of recent development. The problem of this is how the condition of legislation currently on the land associated with land rights of indigenous people and how the shape of the influence of government land policies towards indigenous peoples' land rights. The government at the level of province, District and City with its local wisdom is expected to develop regional regulation that protects the interests on the rights of indegenous people, especially customary land rights based on a legal basis as a form of local government commitment and spirit of regional autonomy. It's time to leave policy that the existence of indigenous people and the strengthening of customary rights to local governments, supported by budget politic. Could be, lack of data and lack of initiative of local governments to conduct an inventory or identification of indigenous people in its territory due to the inadequate allocation of fund and not budgeted in local government budget. Necessary to formulate norms which say that the recognition of indigenous rights as well as a recognition of the existence of customary law community. The main reason because the only thing that can become a subject of customary rights is a customary law community.